Relationship of the Pelvic-Trochanteric Index with greater trochanteric pain syndrome - Leandro Emílio Nascimento Santos (2021)
OBJECTIVES: This study aimed to correlate a higher Pelvic–Trochanteric Index (PTI) with an increased varus of the femoral neck with greater trochanteric pain syndrome (GTPS). The secondary objective was to check whether the pelvic width changes with age. METHODS: A prospective study was conducted to compare female patients diagnosed with GTPS (case group) with asymptomatic female participants (control group) from March 2011 to June 2017. On an anteroposterior pelvic radiograph, lines were drawn by two radiologists, and the PTI (ratio of the distance between the greater trochanters and distance between the iliac crests) was defined and the femoral neck–shaft angle was measured. RESULTS: Data collected based on radiographs of 182 female patients (cases) and 150 female participants (controls) showed that the mean PTI was 1.09 (SD=0.01) in the case group and 1.07 (SD=0.01) in the control group (po0.05), regardless of age. The distance between iliac crests increased with age (po0.05) in symptomatic and asymptomatic individuals. It was also found that the mean femoral neck–shaft angle was 130.6o (SD=0.59) and progression of the varus angulation occurred with age in both groups, with a significance level of 5%. CONCLUSIONS: The PTI was higher in patients with GTPS. The femoral neck–shaft angle does not differ between individuals with and without GTPS; however, it does decrease with age. The pelvic width tends to increase with aging in symptomatic or asymptomatic individuals; therefore, the increase in the pelvic width and decrease in the femoral neck–shaft angle can be interpreted as normal in aging women, which could alter the biomechanics of the hips and pelvis.